2012
DOI: 10.1152/japplphysiol.00051.2012
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic imaging of alveoli using optical coherence tomography needle probes

Abstract: McLaughlin RA, Yang X, Quirk BC, Lorenser D, Kirk RW, Noble PB, Sampson DD. Static and dynamic imaging of alveoli using optical coherence tomography needle probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 61 publications
(60 reference statements)
1
56
0
2
Order By: Relevance
“…24 OCT imaging through core needles (18 Ga), using fast scanning mechanisms, and probe protection that minimizes tissue disruption has been published before. 25 Therefore, OCT imaging may also be considered for guiding biopsies. However, the probe would be more complex, imaging would require a longer acquisition time, and real-time data analysis would require the use of fast parallel processing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…24 OCT imaging through core needles (18 Ga), using fast scanning mechanisms, and probe protection that minimizes tissue disruption has been published before. 25 Therefore, OCT imaging may also be considered for guiding biopsies. However, the probe would be more complex, imaging would require a longer acquisition time, and real-time data analysis would require the use of fast parallel processing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic OCT scans of lungs undergoing simulated respiration have previously been demonstrated in [13], producing a sequence of lung scans at different stages of alveolar expansion and recruitment. Alternatively, Williamson et al [47] demonstrated the acquisition of a series of OCT scans at predefined lung pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue was obtained from animals sacrificed as part of a different research project approved by The University of Western Australia Animal Ethics Committee, and utilized under institutional tissue sharing protocols. Two animals were used in this research: an adult rat, and an adult pig, and imaged according to the protocol described in [13]. The animals were euthanized on the day of the experiment, and dissection was performed immediately post-mortem.…”
Section: Tissue Preparationmentioning
confidence: 99%
See 2 more Smart Citations